(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article is theoretically based on teaching urban air and the requirements for it in the science of Ecology. In addition, the atmosphere is the air shell of the globe, the main sources that ensure the existence of life in the biosphere, and the atmosphere is one of the most important elements of nature, on the basis of which it is much more necessary for the survival of living organisms.